2019
DOI: 10.18632/aging.102092
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from microRNA-199a-overexpressing mesenchymal stem cells inhibit glioma progression by down-regulating AGAP2

Abstract: Accumulating evidence has implied that microRNAs (miRNAs) are implicated in glioma progression, and genetically engineered mesenchymal stem cells can help to inhibit tumor growth of glioma. Herein we hypothesized that miR-199a could be delivered by mesenchymal stem cells to glioma cells through exosomes and thus prevent the glioma development by down-regulating ArfGAP with GTPase domain, ankyrin repeat and PH domain 2 (AGAP2). The expression pattern of miR-199a and AGAP2 was characterized in glioma tissues and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 38 publications
1
48
0
1
Order By: Relevance
“…The NK cell-derived exosomes target GBM cells and play an antitumor role. However, the underlying mechanism remains unclear [ 104 , 112 ]. Hao et al [ 107 ] found that exosomes from the human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) exert partial antitumor activity by regulation of the miR-10a-5p/PTEN signaling.…”
Section: Exosomes In the Treatment Of Gliomasmentioning
confidence: 99%
See 1 more Smart Citation
“…The NK cell-derived exosomes target GBM cells and play an antitumor role. However, the underlying mechanism remains unclear [ 104 , 112 ]. Hao et al [ 107 ] found that exosomes from the human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) exert partial antitumor activity by regulation of the miR-10a-5p/PTEN signaling.…”
Section: Exosomes In the Treatment Of Gliomasmentioning
confidence: 99%
“…Lang et al [ 133 ] isolated the exosomes derived from miR-124a-expressing (via lentiviral expression) MSCs that released miR-124a, which could be used as therapeutic agents against gliomas. A study by Yu et al revealed that the exosomes derived from MSCs transport miR-199a to the glioma cells to downregulate AGAP2 and inhibit glioma cell proliferation, invasion, and metastasis [ 104 ].The overexpression of miR-199a in MSCs improved the chemosensitivity to TMZ, and suppressed glioma cell proliferation. Similarly, Munoz et al demonstrated that the anti-miR-9-delivering exosomes increased the multidrug transporter expression and sensitivity to TMZ in drug-resistant GBM cells, resulting in higher rates of cell death and caspase activity [ 110 ].…”
Section: Exosomes In the Treatment Of Gliomasmentioning
confidence: 99%
“…Another study reported that exosomes from MSCs that overexpress a small interfering RNA against GRP78, which is overexpressed in sorafenib-resistant cancer cells, re-sensitize HCC to sorafenib in vitro and in vivo [150]. Exosomes from miR-119a-overexpressing MSCs suppressed the proliferative, invasive, and migrative activities of glioma cells, resulted in suppression of glioma progression by downregulating ankyrin repeat and PH domain 2 in vitro [151]. Exosomes from miR-16-5p-overexpressing MSCs inhibit the proliferation, migration, and invasion of colorectal cancer cells (CRCs) and promote the apoptosis of such cells by decreasing the expression of integrin α2 in vitro [28].…”
Section: Gene Overexpression To Improve the Function Of Msc-derived Ementioning
confidence: 99%
“…Exosomes from BMSCs overexpressing miR-34 were 2-fold more potent than control MSCs in inducing the inhibition of invasion, migration, proliferation and tumorigenesis of glioblastoma cells, in vitro and in vivo ( Wang B. et al, 2019 ). Exosomes from miR-101-3p and miR-199a-overexpressing BMSCs also inhibited invasion, migration and proliferation of oral cancer cells ( Xie et al, 2019 ) and glioma cells ( Yu et al, 2019 ). Furthermore, inhibition of the tumor progression was also observed in vivo in a glioma model ( Yu et al, 2019 ).…”
Section: Applications In Cancer Treatmentmentioning
confidence: 99%
“…Exosomes from miR-101-3p and miR-199a-overexpressing BMSCs also inhibited invasion, migration and proliferation of oral cancer cells ( Xie et al, 2019 ) and glioma cells ( Yu et al, 2019 ). Furthermore, inhibition of the tumor progression was also observed in vivo in a glioma model ( Yu et al, 2019 ).…”
Section: Applications In Cancer Treatmentmentioning
confidence: 99%